(untitled) (EAAE Annual Conference Proceedings, 2025)
This paper explores the possibilities, techniques and advantages of using the research walking method in architectural education. This modern visual method generates new knowledge based on researchers’ direct experiences and findings. Its use in architectural education is grounded in a rationale of progressive pedagogy, which fosters critical thinking and meaning-making. It’s also about teaching methods based on the multiple intelligence model and the importance of spatial skills in logical thinking, as well as new ways of understanding space that are intuitive and creative. Research walking enables architectural spaces to be considered not as abstract, algorithmic products, but as complex multimodal environments whose elements are meaningful places rather than buildings. Walking methods diverge starkly from walking data (whether through the use of GPS or an emphasis on mobility); they are qualitative, highly engaging methodologies frequently employed in participatory design and environmental research. Rather than empathising with users, the rationale is that researchers become users themselves for the duration of the walk. Walking and noting impressions provides a distinctive ethnographic viewpoint, blending time commitment with careful observation and discussion. The observations in this work were largely based on teaching experience with architecture students. A mixed, partly structured walking methodology was employed, combining techniques such as walking observations, interviews, photo stories and transect walks, while analysing selected buildings for public use in Cracow. This methodology involved repetitive walks employing different modes of action. On the one hand, there was more aimless walking, focusing on its stimulating nature and incorporating photography and group discussions. On the other hand, there was more structured research walking, involving the use of a questionnaire and observational notes to take an inventory of the analysed space. The reflections gathered during the latter were transformed into specific data on contextual relationships, accessibility, clarity, responsiveness and human scale. Overall, the observational information gathered during these walks revealed unexpected contexts for spatial and social interactions, offering students the chance to communicate their positionality and acknowledge their context.